Fabrication and characterisation of poly (ethylene-co-vinyl alcohol) nanofibers with biocidal additive for water filtration - Motsi, Margaret (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.